1879 Mo. Laws 90 - (:unkn) unknown (My University, 1879)
An Act To Prohibit The Discharge Of Firearms In The Immediate Vicinity Of Any Courthouse, Church Or Building Used For School Or College Purposes, § 1: Hereafter it shall be unlawful for any person in this State, except he be a sheriff or other officer, in the discharge of official duty to discharge or fire off any gun, pistol or fire-arms of any description in the immediate vicinity of any court house, church or building used for school or college purposes.
Keywords: DISCHARGE